Reprogramming of Mice Primary Hepatocytes into Insulin-Producing Cells by Transfection with Multicistronic Vectors - Haizhao Luo; Rongping Chen; Rui Yang; Yan Liu; Youping Chen; Yi Shu; Hong Chen (Journal of Diabetes Research)
The neogenesis of insulin-producing cells (IPCs) from non-beta-cells has emerged as a potential method for treating diabetes mellitus (DM). Many groups have documented that activation of pancreatic transcription factor(s) in hepatocytes can improve the hyperglycemia in diabetic mice. In the present study, we explored a novel protocol that reprogrammed primary hepatocytes into functional IPCs by using multicistronic vectors carrying pancreatic and duodenal homeobox-1 (Pdx1), neurogenin 3 (Ngn3), and v-musculoaponeurotic fibrosarcoma oncogene homolog A (MafA). These triple-transfected cells activated multiple beta-cell genes, synthesized and stored considerable amounts of insulin, and released the hormone in a glucose-regulated manner in vitro. Furthermore, when transplanted into streptozotocin-induced diabetic mice, the cells markedly ameliorated glucose tolerance. Our results indicated that ectopic expression of Pdx1, Ngn3, and MafA facilitated hepatocytes-to-IPCs reprogramming. This approach may offer opportunities for treatment of DM.